Women, Work, and Protest in the Italian Diaspora: An International Research Agenda - Gabaccia, Donna; Iacovetta, Franca (Labour / Le Travail, 1998)
Interrogates the currents of scholarly inquiry into the Italian emigration of the 19th and 20th centuries. Argues for a woman-centred, gendered, and proletarian history of this diaspora, and suggests new areas of investigation.

A Nation of Immigrants: Women, Workers, and Communities in Canadian History, 1840s-1960s - Iacovetta, Franca; Draper, Paula; Ventresca, Robert (University of Toronto Press, 1998)
This collection brings together a wide array of writings on Canadian immigrant history, including many highly regarded, influential essays. Though most of the chapters have been previously published, the editors have also commissioned original contributions on understudied topics in the field. The readings highlight the social history of immigrants, their pre-migration traditions as well as migration strategies and Canadian experiences, their work and family worlds, and their political, cultural, and community lives. They explore the public display of ethno-religious rituals, race riots, and union protests; the quasi-private worlds of all-male boarding-houses and of female domestics toiling in isolated workplaces; and the intrusive power that government and even well-intentioned social reformers have wielded over immigrants deemed dangerous or otherwise in need of supervision.Organized partly chronologically and largely by theme, the topical sections will offer students a glimpse into Canada's complex immigrant past. In order to facilitate classroom discussion, each section contains an introduction that contextualizes the readings and raises some questions for debate. A Nation of Immigrants will be useful both in specialized courses in Canadian immigration history and in courses on broader themes in Canadian history. –Publisher's description. Contents: The Irish in nineteenth-century Canada: class, culture, and conflict – American Blacks in nineteenth-century Ontario: challenging the stereotypes – Settling the Canadian West: the 'exotic' continentals – 'Women's work': paid labour, community-building, and protest – Men without women: 'bachelor' workers and gendered identities – Demanding rights, organizing for change: militants and radicals – Encountering the 'other': society and state responses, 1900s-1930s – Regulating minorities in 'hot' and 'cold' war contexts, 1939-1960s.
Book available at Internet Archive to people with print disabilities: https://archive.org/details/nationofimmigran00iaco/page/n3/mode/2up